[mu-1,2-Bis(diphenylphosphino)methane-kappa P-2:P `]bis{[(Z)-O-ethyl N-(4-nitrophenyl)thiocarbamato-kappa S]gold(I)} - Ho, S.Y.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Each gold atom in the binuclear title compound, [Au-2(C9H9N2O3S)(2)(C25H22P2)], is coordinated within an S,P-donor set that defines a slightly distorted linear geometry [S-Au-P angles = 172.77 (6) and 173.84 (6)degrees], with the distortion due in part to a close intramolecular Au center dot center dot center dot O contact [2.968 (11) and 2.963 (4) angstrom]. The molecule adopts a U-shaped conformation allowing for the formation of an aurophilic Au center dot center dot center dot Au interaction [3.2320 (5) angstrom]. Molecules are consolidated in the crystal structure by C-H center dot center dot center dot pi interactions. Disorder was noted for one of the ethoxy groups with two orientations being resolved in a 0.679 (16):0.321 (16) ratio.